A Web Application for the Photon Strength Function Database - Jongile S.; Marian L.; Dimitriou P.; Wiedeking M. (EPJ Web of Conferences)
A specialized web application has been developed to manage, query, and visualize photon strength function (PSF) data, compiled as a part of an IAEA Coordinated Research Project. This application significantly advances accessibility and interaction with the data over existing platforms, improving upon the capabilities of the prior resource. Central to this application is the database structure, crucial for efficient data management and retrieval. Built using the Django framework, the Web application’s user interface presents queried data and search results in an accessible format. t provides details on basic nuclear properties, including the atomic number (Z), mass number (A), multipolarity, energy range, and the experimental methods used. In addition, the application offers functionalities for searching and sorting data by author names or publication years, facilitating refined navigation through the extensive PSF data repository. A notable feature is the dynamic data visualization tool that utilizes Plotly to create interactive graphs. The platform also features a comprehensive data processing pipeline that ensures data integrity and accessibility.